Effects of Wordwall Interactive Media on Grade III Arts and Culture Learning Outcomes - Nurfaiza, Nurfaiza; Lagandesa, Yun Ratna; Pahriadi, Pahriadi; Dewi, Andi Imrah; Rahmaeni, Andi; Wilade, Surahman (Papanda Publisher, 2025)
This study examined the effectiveness of Wordwall interactive media on learning outcomes in Arts, Culture, and Crafts (SBdP) among third-grade elementary students. A pre-experimental design with one-group pretest-posttest was employed, involving 25 students at SD Inpres 1 Kawatuna, Palu, Indonesia, during the 2024/2025 academic year. The intervention consisted of three instructional sessions implementing Wordwall-based activities focused on decorative drawing concepts. Data were collected through validated achievement tests (Cronbach's Alpha = 0.784), observation checklists, semi-structured interviews, and documentation. Statistical analyses using SPSS 25 included descriptive statistics, Shapiro-Wilk normality tests, paired-samples t-tests, and normalized gain calculations. Results demonstrated significant improvement from pretest (M = 54.74, SD = 14.04) to posttest (M = 84.21, SD = 11.88), with t(24) = -11.705, p < .001. The mean N-gain score of 0.826 (82.59%) indicated high learning effectiveness according to Hake's classification. These findings suggest that Wordwall significantly enhances student engagement, motivation, and achievement in arts education. However, the single-group design limits causal inferences, as observed improvements may reflect multiple factors including novelty effects and teacher enthusiasm. Future research should employ randomized controlled trials, longitudinal designs, and comparative studies across diverse contexts to establish more robust evidence. Despite methodological limitations, this study contributes valuable preliminary evidence supporting interactive digital media integration in elementary arts and culture education.